E3SMv0‐HiLAT: A Modified Climate System Model Targeted for the Study of High‐Latitude Processes. (26th August 2019) - Hecht, Matthew; Veneziani, Milena; Weijer, Wilbert; Kravitz, Ben; Burrows, Susannah; Comeau, Darin; Hunke, Elizabeth; Jeffery, Nicole; Urrego‐Blanco, Jorge; Wang, Hailong; Wang, Shanlin; Zhang, Jiaxu; et al.
Abstract: We document the configuration, tuning, and evaluation of a modified version of the Community Earth System Model version 1 (Hurrell et al., 2013, https://doi.org/10.1175/BAMS-D-12 ), introduced here as E3SMv0‐HiLAT, intended for study of high‐latitude processes. E3SMv0‐HiLAT incorporates changes to the atmospheric model affecting aerosol transport to high northern latitudes and to reduce shortwave cloud bias over the Southern Ocean. An updated sea ice model includes biogeochemistry that is coupled to an extended version of the ocean model's biogechemistry. This enables cloud nucleation to depend on the changing marine emissions of aerosol precursors, which may be expected in scenarios with strongly changing sea ice extent, oceanic stratification and associated nutrient availability, and atmospheric state. An evaluation of the basic preindustrial state of E3SMv0‐HiLAT is presented in order to ensure that its climate is adequate to support future experimentation. Additional capability is not achieved without some cost, relative to the extraordinarily well‐tuned model from which it was derived. In particular, a reduction of bias in cloud forcing achieved over the Southern Hemisphere also allows for greater Southern Ocean sea ice extent, a tendency that has been partially but not fully alleviated through experimentation and tuning. The most interesting change in the behavior of the model may be its response to greenhouse gas forcing: While the climate sensitivity is found to be essentially unchanged from that of Community Earth System Model version 1, the adjusted radiative forcing has increased from within one standard deviation above that of Coupled Model Intercomparison Project Phase 5 models to nearly two standard deviations. Key Points: New Earth system model configuration features improved treatment of sea ice and aerosols Extended marine biogeochemistry enables cloud nucleation to depend on prognostic marine emissions Climate sensitivity is little changed, but adjusted radiative forcing is stronger in modified model